Prognostic Values Of Preoperative Serum CEA And CA125 Levels And Nomograms For Young Breast Cancer Patients - Li, Xuan (Onco Targets Ther, 2019)
BACKGROUND: Young breast cancer patients have poor prognosis compared to older patients in both overall survival (OS) and loco-regional failure-free survival. Carcinoembryonic antigen (CEA) and Cancer antigen 125 (CA125) have been widely used, but their prognostic value in young breast cancer patients remains unknown. The objectives of this study were to evaluate the prognostic value of preoperative CEA and CA125 serum levels and to build nomograms for better prognostic prediction of young Chinese breast cancer patients using both tumor markers. METHODS: We included 576 young breast cancer patients (≤40 years at diagnosis) and collected their preoperative information. The best cut-off values of the CEA and CA125 were identified with receiver operating characteristic (ROC) curves. Univariate and multivariate analyses were used to identify the relative risks of factors for the overall survival (OS), and disease-free survival (DFS), and nomograms were constructed based on these identified factors. RESULTS: The best cut-off values for CEA and CA125 in young breast cancer patients was 3.38 ng/mL and 19.38 U/mL, respectively. Kaplan-Meier analysis showed that young patients with low levels of CEA and/or CA125, had longer OS and DFS. Multivariate analysis suggested that both CEA and CA125 levels were independent predictive elements for OS. Nomograms were built and showed a better predictive ability for OS (AUC = 0.856) and DFS (AUC = 0.702) in young breast cancer patients. CONCLUSION: Preoperative serum CEA and CA125 levels could be the independent prognostic factors for OS, and the nomograms including these two variables provide more personal forecasts information to help physicians optimize treatment for young breast cancer patients better.